On \(fgspr\)-Closed and \(fgspr\)-Open Mappings (Journal of Informatics and Mathematical Sciences, 2017)
The purpose of this paper is to introduce a new type of fuzzy generalized mappings namely \(fgspr\)-closed mappings, \(fgspr\)-open mappings, \(fgspr^*\)-closed mappings and \(fgspr^*\)-open mappings in fuzzy topological spaces and study some of their properties.
Keywords: \(fgspr\)-closed map; \(fgspr\)-open map; \(fgspr^*\)-closed map; \(fgspr^*\)-open map